Bone-borne accelerated sutural expansion: A microcomputed tomography study in rabbits - Alyessary, Akram S.; Yap, Adrian U-Jin; Othman, Siti Adibah; Ibrahim, Norliza; Rahman, Mohammad Tariqur; Radzi, Zamri (Elsevier, 2018)
Introduction: In this study, we evaluated the effect of bone-borne accelerated expansion protocols on sutural separation and sutural bone modeling using a microcomputed tomography system. We also determined the optimum instant sutural expansion possible without disruption of bone modeling. Methods: Sixteen New Zealand white rabbits, 20 to 24 weeks old, were randomly divided into 4 experimental groups. Modified hyrax expanders were placed across their interfrontal sutures and secured with miniscrew implants located bilaterally in the frontal bone. The hyrax appliances were activated as follows: group 1 (control), 0.5-mm per day expansion for 12 days; group 2, 1-mm instant expansion followed by 0.5 mm per day for 10 days; group 3, 2.5-mm instant expansion followed by 0.5 mm per day for 7 days, and group 4, 4-mm instant expansion followed by 0.5 mm per day for 4 days. After 6 weeks of retention, sutural separation and sutural bone modeling were assessed by microcomputed tomography and quantified. Statistical analysis was performed using Kruskal Wallis and Mann-Whitney U tests and the Spearman rho correlation (P <0.05). Results: Median amounts of sutural separation ranged from 2.84 to 4.41 mm for groups 1 and 4, respectively. Median bone volume fraction ranged from 59.96% to 69.15% for groups 4 and 3, respectively. A significant correlation (r = 0.970; P <0.01) was observed between the amounts of instant expansion and sutural separation. Conclusions: Pending histologic verifications, our findings suggest that the protocol involving 2.5 mm of instant expansion followed by 0.5 mm per day for 7 days is optimal for accelerated sutural expansion. When 4 mm of instant expansion was used, the sutural bone volume fraction was decreased.